Differentiation and gene expression profile of tumor-associated macrophages - Schmieder, Astrid; Michels-Zetsche, Julia D.; Schönhaar, Kathrin; Goerdt, Sergij; Schledzewski, Kai (Seminars in cancer biology, 2012)
Tumor microenvironment is composed of proliferating neoplastic cells, a vascular network of endothelial cells, extra cellular matrix produced by fibroblasts, cellular compartments of adaptive immunity like lymphocytes and dendritic cells as well as cells of innate immunity, e.g., natural killer cells and macrophages. Many pre-clinical and clinical studies demonstrate an inversed correlation between macrophage infiltrate and patients’ prognosis indicating a macrophage supporting role for tumor progression as producers of growth and angiogenic factors and as regulators of tissue remodelling. Based on in vitro models, macrophages have been classified in pro-inflammatory, classically activated macrophages (M1; stimulated by IFN-γ or LPS) and anti-inflammatory, alternatively activated macrophages (M2; stimulated by either IL-4/IL-13, IL-1β/LPS in combination with immune complexes or by IL-10/TGFβ/glucocorticoids). Tumor escape has been linked with a switch from M1 activation in the early tumor initiation process towards M2-like phenotype during tumor progression, a process that highlights the heterogeneity and plasticity of macrophage activation and which offers a possible therapeutic target directed against reversing the TAM phenotype in the tumor. Here, we review different tumor-environmental stimuli and signalling cascades involved in this switch in differentiation and the so connected gene regulation in TAMs. In addition, therapeutic applications deducted from this differentiation and gene regulatory processes are presented. Data from pre-clinical as well as clinical studies clearly support the notion, that TAMs are excellent novel therapeutic targets for the fight against cancer.
Gesehen am 06.06.2018